AN ANALYSIS OF LEVEL CUSTOMER SATISFACTION ON QUALITY AND TASTE VILLAGE COCONUT JELLY BEVERAGE PRODUCTS - Firgiawan Tenriadi; Nabila Yudisha; Margie Subahagia Ningsih (Sean Institute, 2023)
The development of local beverage products is currently very rapid. This is marked by the emergence of many different brands and types of local beverage products circulating in the market so that there is a need for strong competitiveness. Customer loyalty is the key to success because customer loyalty has a strategic value for the industry and is one of the assets of high-value products. Coconut Jelly is one of the MSMEs involved in the beverage and food sector. The processed coconut processing system has become one of the selling points of local entrepreneurs to develop the coconut fruit beverage sector. A new breakthrough in processing young coconuts into coconut jelly. In this study will discuss the level of customer satisfaction with the quality and taste of the product using quantitative methods taken from field survey data.